Mac kung fu : over 400 tips, tricks, hints, and hacks for Apple OS X - Thomas, Keir (Pragmatic programmers., 2012)
Squeeze every drop of juice from OS X with over 400 quick and easy tips, tricks, hints and hacks in Mac Kung Fu: Second Edition . Exploit secret settings and hidden apps, push built-in tools to the limit, radically personalize your Mac experience, and make "it just works" even better. In addition to core OS X technologies, this significantly revised and expanded update to the best-selling first edition dissects new OS X Mountain Lion tools such as iCloud, Notifications, Reminders, and Calendar. Mac Kung Fu: Second Edition will blow your mind with secret hacks never before made public and little-known tricks that will change the way you work forever. From big tasks through everyday jobs, this book will improve your productivity and refine your workflow. You'll customize and manage the OS X interface, boost the power of built-in apps, efficiently handle the filesystem, implement important security tricks, and much more. Working with files in iCloud? We have tips to help. Managing program windows on your desktop? Hacks will make life easier. Creating reminders or notes? Use our tricks to make the process more productive. Emailing, tweeting, browsing, printing, word processing, testing and exploiting hardware, working with photos, movies, and documents ... There's no area Mac Kung Fu: Second Edition doesn't touch upon, making it a unique and utterly necessary addition for any Mac lover's bookshelf. Each tip is deliberately short and readable, often detailing things even Mac Geniuses don't know, and you can dip in and out whenever you want. Most tips take less than a minute to complete, yet the results last for a lifetime of better computing. What You Need:A Mac running OS X Mountain Lion and above